1969
DOI: 10.1111/j.1469-8137.1969.tb06463.x
|View full text |Cite
|
Sign up to set email alerts
|

Aeropalynology in Britain—an Outline

Abstract: SUMMARYThe author reasserts his original definition of palynology as the study of plant spores and their dispersal and applications thereof, and here considers aeropalynology as that branch of palynology which is concerned with the dissemination of plant spores in both theory and practice. During the present century important advances in methods of sampling atmospheric spores have been made and have been applied at a limited number of locations in England, Wales and Scotland either with a view to assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…Hyde and Williams have conducted research on the air-borne pollen in Britain from the point of view of allergy since 1933 (Hyde 1969). Gregory has studied air-borne fungus spores in Britain since 1945 (Hyde 1969). Recently, Nilsson et al (1977) reported air-borne pollen grains and spores of 74 species distributed in Northern Europe.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hyde and Williams have conducted research on the air-borne pollen in Britain from the point of view of allergy since 1933 (Hyde 1969). Gregory has studied air-borne fungus spores in Britain since 1945 (Hyde 1969). Recently, Nilsson et al (1977) reported air-borne pollen grains and spores of 74 species distributed in Northern Europe.…”
Section: Introductionmentioning
confidence: 94%
“…Other researches on the daily census of air-borne pollen has been reported (Hyde 1952, Deshpande & Chitaley 1976). Hyde and Williams have conducted research on the air-borne pollen in Britain from the point of view of allergy since 1933 (Hyde 1969). Gregory has studied air-borne fungus spores in Britain since 1945 (Hyde 1969).…”
Section: Introductionmentioning
confidence: 98%
“…Based on the data, Hyde published an atlas of airborne pollen grains of the UK [36-38]. The dominant pollen types recorded from the UK are Alnus , Artemisia , Betula , Corylus , Quercus , Fagus , Pinus , graminae and others [39-41].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobiological survey in UK was initiated at Cardiff by Hyde and Williams [ 36 ], which was later extended to several other stations in Great Britain. Based on the data, Hyde published an atlas of airborne pollen grains of the UK [ 36 - 38 ]. The dominant pollen types recorded from the UK are Alnus , Artemisia , Betula , Corylus , Quercus , Fagus , Pinus , graminae and others [ 39 - 41 ].…”
Section: Introductionmentioning
confidence: 99%